Madagascar : Staff Report for the 2002 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility, and Requests for Extension of Arrangement, Waiver of Performance Criteria, and for Interim Assistance under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2003)
This paper examines Madagascar's 2002 Article IV Consultation, Second Review Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Extension of Arrangement. Madagascar's performance under the PRGF-supported program in 2001 was strong, with the exception of weak revenue collection, an issue that the new government has begun to address. The budget for 2003 is consistent with the macroeconomic constraints, and places an appropriate emphasis on revenue mobilization and on wage restraint. Administrative procedures need to be streamlined to ensure faster expenditure commitment and execution of donor-funded projects.